2002
DOI: 10.1002/eqe.217
|View full text |Cite
|
Sign up to set email alerts
|

Sliding fragility of block‐type non‐structural components. Part 1: Unrestrained components

Abstract: SUMMARYMotivated by the development of performance-based design guidelines with emphasis on both structural and non-structural systems, this paper focuses on seismic vulnerability assessment of block-type unrestrained non-structural components under sliding response on the basis of seismic inputs speciÿed by current seismic codes. Two sliding-related failure modes are considered: excessive relative displacement and excessive absolute acceleration. It is shown that an upper bound for the absolute acceleration r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(34 citation statements)
references
References 10 publications
(6 reference statements)
2
31
1
Order By: Relevance
“…Past research has indicated that the sliding motion is sensitive to the frequency content of its input excitation (Augusti et al 1992;Lopez Garcia and Soong 2003). Our results indicate that the intensity of input acceleration increased from level 1 to level 2 by 22% on average, while the sliding displacements increased on average by 85%.…”
Section: Effect Of Floor Elevation For Display Case 2 On Hardwood Floorsupporting
confidence: 47%
“…Past research has indicated that the sliding motion is sensitive to the frequency content of its input excitation (Augusti et al 1992;Lopez Garcia and Soong 2003). Our results indicate that the intensity of input acceleration increased from level 1 to level 2 by 22% on average, while the sliding displacements increased on average by 85%.…”
Section: Effect Of Floor Elevation For Display Case 2 On Hardwood Floorsupporting
confidence: 47%
“…An important step in estimating the vulnerability of acceleration sensitive NCSs and thus improving their probability of survival, is to estimate the expected peak horizontal floor acceleration (PHFA) distribution within the buildings housing these components as accurately as possible. Subsequently, knowledge of PHFA can be used to assess the seismic vulnerability of NCSs via seismic fragility curves, which are derived from damage data, if available, or experimental and/or numerical simulations [e.g., RayChaudhuri and Hutchinson, 2005, Lopez-Garcia and Soong 2003aBadilloAlmaraz et al, 2007]. Therefore, a better prediction of PHFA leads to a better design or retrofitting strategy for anchoring, supporting, or bracing the NCS.…”
Section: Introductionmentioning
confidence: 99%
“…Sliding is very common for freestanding (i.e., unrestrained) EC, particularly those that are stocky and have a relatively low friction coefficient. The problem of sliding objects has been studied at various levels by Shao and Tung , Choi and Tung , Lopez Garcia and Soong , Chaudhuri and Hutchinson , Hutchinson and Chaudhuri , Konstantinidis and Makris , and references reported therein. The concern for sliding EC is excessive displacements, which can lead to different problems depending on the type of EC.…”
Section: Introductionmentioning
confidence: 99%